Type I Arabinogalactan and Methyl-Esterified Homogalacturonan Polysaccharides from Tamarillo (Solanum betaceum cav.) Fruit Pulp Ameliorate DSS-Induced Ulcerative Colitis - Lara Luisa Valerio de Mello Braga; Carolina Silva Schiebel; Gisele Simão; Karien Sauruk da Silva; Mateus Henrique dos Santos Maia; Ana Carolina Vieira Ulysséa Fernardes; Georgia E. do Nascimento; Lucimara Mach Côrtes Cordeiro; Tufik Adel Issa; Marcelo Biondaro Gois; Elizabeth Fernandes Soares; Daniele Maria-Ferreira (Pharmaceuticals)
Background: Inflammatory bowel diseases, such as ulcerative colitis and Crohn’s disease, affect the gastrointestinal tract. Treatment aims to induce remission and relieve symptoms but may fail or cause side effects. Recent studies suggest that natural polysaccharides can reduce inflammation and promote healing. The polysaccharides of the pulp of tamarillo (Solanum betaceum cav.) have shown beneficial effects, but their potential in colitis is still unexplored. Objective: To investigate the effect of polysaccharides from tamarillo pulp in an animal model of ulcerative colitis. Methods: Polysaccharides from tamarillo pulp (STWA) were extracted and tested in female mice (BALB/c) to investigate their effect on dextran sodium sulfate (DSS)-induced ulcerative colitis. Different doses of the polysaccharides were tested (10 mg/kg, 30 mg/kg, and 100 mg/kg). The course of the disease and the weight of the animals were monitored daily. At the end of the experimental protocol, the large intestine was removed and measured. Markers of oxidative stress and inflammation were then analyzed. Histological analysis was performed to assess microscopic changes. Results: Treatment with STWA (100 mg/kg) prevented weight loss in mice with DSS-induced colitis and reduced the disease activity index. The colon length was preserved, and occult blood in the feces was reduced. Treatment with STWA controlled oxidative stress. Glutathione S-transferase (GST) levels increased, while lipid peroxidation decreased. The inflammatory process was reduced, as indicated by the decrease in myeloperoxidase (MPO), N-acetylglucosamine (NAG), and tumor necrosis factor alpha (TNF-α) levels and the increase in interleukin 10 (IL-10) levels. STWA also improved the colon histology, while preserving the colonic epithelium. Conclusions: The results suggest that STWA has protective potential and reduces inflammation in an experimental model of ulcerative colitis in mice.